Chromosome aberrations during in-vitro labeling of red blood cells with 99mTc: a study with cytokinesis block micronucleus assay in human peripheral blood lymphocytes. Issue 12 (December 2020) - Martinez, Teresa; Abella Tarazona, Alejandra; Garcia Aliaga, Angeles
Abstract : Radiopharmaceuticals are special medicines composed by a radionuclide and a non-radioactive compound characterized by non-pharmacodynamic effects, low prevalence of side effects, and a possible risk of oncogenesis, since its administration to patients supposes a radiation dose to organism. Over these years, radiation damage induced by diagnosis radiopharmaceuticals has been evaluated, including the radiolabeled autologous cells, a group of radiopharmaceuticals where blood cells extracted from patients are labeled in-vitro and readministered for diagnosis. There is not a consensus about the possibility of increasement of risk for malignancies associated with the radiolabeled blood cells, so for a more accurate evaluation of the potential oncogenic risk related to the administration of [ 99m Tc]Tc labeled red blood cells, radiation dose received by the cells during the labeling process is studied by means of the cytokinesis-blocked micronucleus (CBMN) assay and a dose-response curve constructed by in-vitro external irradiation of blood samples. Our work enables to establish the range of activity to be added during the in-vitro labeling of red blood cells with [ 99m Tc]Tc pertechnetate to avoid radiation damage to cells. Activities recommended for blood volume determination and angiography do not increase the risk of malignancies, whilst activities of 370 MBq show chromosome aberrations in lymphocytes. Evaluation of the radiation damage related to the in-vitro labeling is recommended to estimate the potential oncogenic risk and minimize it.